2019
DOI: 10.1080/20008198.2018.1558709
|View full text |Cite
|
Sign up to set email alerts
|

The association between disaster exposure and media use on post-traumatic stress disorder following Typhoon Hato in Macao, China

Abstract: Background: Direct exposure to natural disasters and related losses are associated with post-traumatic stress disorder (PTSD). It is less clear whether indirect media exposure is associated with PTSD.Objective: This study investigated key exposure-related risk factors for PTSD and examined the effect of media exposure on the prevalence of disaster-related PTSD.Method: Typhoon Hato directly hit Macao on 23 August 2017. It was one of the most serious natural disasters ever to strike southern China. One month aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
81
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 42 publications
12
81
0
2
Order By: Relevance
“…Another study conducted in Macao was to see the association of natural disaster exposure by media on trauma. Findings shows that, people who attached with media have higher tendency to experience trauma compared those who are not [31]. These findings also supported by other studies conducted in US that some types of media use and certain media content following a natural disaster are associated with traumatized.…”
Section: Discussionsupporting
confidence: 82%
“…Another study conducted in Macao was to see the association of natural disaster exposure by media on trauma. Findings shows that, people who attached with media have higher tendency to experience trauma compared those who are not [31]. These findings also supported by other studies conducted in US that some types of media use and certain media content following a natural disaster are associated with traumatized.…”
Section: Discussionsupporting
confidence: 82%
“…In Tunisia as in different parts of the world, COVID-19 crisis have resulted in panic buying of essential consumer items (including semolina, flour and cleaning products), leading to exhaustion of resources. Prior research has demonstrated that lack of necessities as well as financial loss are consistent predictors of PTSD (Hall et al, 2019).…”
Section: To the Editormentioning
confidence: 99%
“…Furthermore, we now have a new peri-and posttraumatic factor: social media (Hall et al, 2019). The rest of the world watches the disaster as it unfolds, and the conceptualization of criterion A may be challenged by the social media's inbuilt possibilities to witness aversive details of the disaster through the smartphones of those present.…”
Section: Mass Trauma and Early Interventionsmentioning
confidence: 99%